Design and development of bio-medical devices using rapid prototyping techniques - Chua, Chee Kai. (2008)
Drug releases in therapeutic treatment must be carefully controlled as they have a direct impact on the effectiveness of the treatment. However, existing drug delivery systems are either too complicated to be self-administered or face low compliance by patients. There has been lots of research done in the pharmaceutical field to characterize and optimize drug delivery devices (DDD) built by traditional methods. These methods however, still lack flexibility in that drugs cannot be distributed within the device according to desired patterns, which critically controls the rate and amount of drug released.